1996
DOI: 10.1111/j.1365-2915.1996.tb00750.x
|View full text |Cite
|
Sign up to set email alerts
|

Phenology of Stomoxyinae in a Kenyan forest

Abstract: The biology of nineteen taxa of African Stomoxyinae was studied during experiments with odour-baited Vavoua traps in Nairobi National Park, Kenya. Both male and female Stomoxys were captured in similar numbers with CO2 released at 2 l/min or octenol released at 2 mg/h. Some species of Haematobosca reacted synergistically to a combination of these attractants, producing large increases in catch. Stygeromyia and Rhinomusca responded only to CO2 and Prostomoxys did not respond to either bait. Many different activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0
1

Year Published

1998
1998
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 27 publications
0
29
0
1
Order By: Relevance
“…Most of the test compounds did not affect trap catch, though 1-octen-3-ol yielded mixed results and sometimes was associated with increased (about 3-fold) catch, especially at high doses (2 mg/hr). In a similar study, Mihok et al (1996) did not find a consistent effect for 1-octen-3-ol. In two experiments it did not enhance catch of Stomoxys compared to CO 2 alone, and when released by itself caught less than half the number of flies as a CO 2 -baited trap, which is similar to the outcome for a CO 2 -baited Vavoua trap against an unbaited trap.…”
Section: Olfaction In Vector-host Interactions 301mentioning
confidence: 79%
See 1 more Smart Citation
“…Most of the test compounds did not affect trap catch, though 1-octen-3-ol yielded mixed results and sometimes was associated with increased (about 3-fold) catch, especially at high doses (2 mg/hr). In a similar study, Mihok et al (1996) did not find a consistent effect for 1-octen-3-ol. In two experiments it did not enhance catch of Stomoxys compared to CO 2 alone, and when released by itself caught less than half the number of flies as a CO 2 -baited trap, which is similar to the outcome for a CO 2 -baited Vavoua trap against an unbaited trap.…”
Section: Olfaction In Vector-host Interactions 301mentioning
confidence: 79%
“…Hoy (1970) reported that Malaise traps releasing CO 2 at 3 l/min caught about three times more stable flies than unbaited traps, and Roberts (1972) reported that catches from a Malaise trap baited with 3.5 l/min CO 2 were similar to those from a trap baited with odour from a single steer. More recently, Mihok et al (1996) found that Vavoua traps baited with CO 2 at 2 l/min caught about twice as many Stomoxyinae flies as unbaited traps. Some of the early work on tsetse responses to odour also yielded useful information for Stomoxyinae.…”
Section: Field Work On the Responses Of Stomoxyinae To Host Odourmentioning
confidence: 99%
“…For example, catches of Tabanidae, Stomoxyinae and non-biting Muscidae were increased 7-20 times at 2.5 l min -1 and 38-47 times at 15 l min -1 in extensive electric net experiments with visual targets in Zimbabwe (Vale, 1980). Carbon dioxide can also act synergistically with attractants such as acetone and 1-octen-3-ol to produce large increases in catch for tsetse (Torr et al, 1995), and other Diptera (Mihok et al, 1996).…”
Section: Discussionmentioning
confidence: 91%
“…Mavoungou et al (2008) described S. niger bilineatus and S. niger niger as sympatric species, the former being abundant in savannas with abundant wild fauna, while the latter is more associated with anthropized area. Mihok et al (1996) also pointed out differences in habitat affinities, sex ratio and activity patterns between these species. Given morphological observations, ecological isolation and molecular data, it appears very likely that S. niger niger and S. niger bilineatus belong to different species.…”
Section: Phylogenetic Relationships and Taxonomy Of The Stomoxys Groupmentioning
confidence: 97%